Advanced nanomaterials for aerospace applications - Cabrera, Carlos R.; Miranda, Félix A. (Pan Stanford Publishing, 2015)
Advanced Nanomaterials for Aerospace Applications has been developed for a community interested in space science and nanotechnology. Scientists and engineers from several NASA field centers and the Jet Propulsion Laboratory, University of Puerto Rico, The Pennsylvania State University, and INFN-Laboratori Nazionali di Frascati, Italy, have joined efforts to discuss the applications of nanomaterials in sensors, atmosphere revitalization in habitable space platforms, life support systems, regenerative fuel cells, lithium-ion batteries, robust lightweight materials, nanoelectronics, and electromagnetic shielding. The book concludes with chapters that discuss bringing NASA-relevant nanotechnology into the classroom and the future directions in nanotechnology research and development at NASA.